Chey-ol: new variety of oleic safflower for northwest Mexico - Casillas Eva Ávila; Ocho Espinoza Xóchitl Militza; Montoya Coronado, Lope; Aguilera Molina Néstor Alberto; Borbón Gracia Alberto; Alvarado Padilla Jorge Iván (Revista Mexicana de Ciencias Agrícolas, 2017)
Chey-ol is a variety of safflower (Carthamus tinctorius L.) oleic type, which was generated through Safflower breeding program, at the Experimental Field Norman E. Borlaug, of the INIFAP, in coordination with the experimental fields of CIRNO and other safflower producing regions, it was registered under the number CAR-020-250615 in the National Catalog of Plant Varieties (CNVV). As response to the demands of producers and industries the variety was obtained with a potential yield of 4 t ha-1 and an oil content of 40%. Chey-ol outperformed the Ciano-ol control material, both in yield and in the quality and quantity of oleic type oil. Chey-ol can be sown during the autumn-winter cycle throughout the Northwest region of México such as: Sonora, Sinaloa, Baja California and Baja California Sur.